Accelerated knee osteoarthritis is associated with pre-radiographic degeneration of the extensor mechanism and cruciate ligaments: data from the Osteoarthritis Initiative. - Davis, Julie E.; Harkey, Matthew S.; Ward, Robert J.; MacKay, James W.; Lu, Bing.; Price, Lori Lyn.; Eaton, Charles B.; Lo, Grace H.; Barbe, Mary F.; McAlindon, Timothy E.; Driban, Jeffrey B. (Tufts University. Tisch Library., 2019)
Background: To determine if adults with incident accelerated knee osteoarthritis (KOA) are more likely to have degenerative knee ligaments or tendons compared to individuals with typical or no KOA.; Keywords: Epidemiology, Knee, Osteoarthritis, Ligaments, Tendons.; Springer Open.